Increased C reactive protein and cardiac enzyme levels after coronary stent implantation. Is there protection by remote ischaemic preconditioning?. Issue 12 (19th July 2006) - Iliodromitis, E K; Kyrzopoulos, S; Paraskevaidis, I A; Kolocassides, K G; Adamopoulos, S; Karavolias, G; Kremastinos, D T
Abstract : Aim: To investigate whether remote ischaemic preconditioning (RIPC) can attenuate the inflammatory response and enzyme leakage that can occur after uncomplicated routine percutaneous coronary intervention (PCI). Methods: 41 consecutive normotensive patients with stable angina and single-vessel disease were assigned to be exposed to RIPC (n = 20) or not (control group; n = 21) before elective PCI with stent implantation. RIPC was induced by three cycles of 5-min ischaemia–reperfusion of both upper limbs (inflation/deflation of blood pressure cuff). C reactive protein (CRP), creatine phosphokinase (CK), CK cardiac isoenzyme (CK-MB) and troponin I (TNI) were serially measured for 48 h. Results: No difference in baseline values was observed between the groups. The CRP rose significantly (p<0.001) and at 48 h was similarly increased (>fourfold) in both groups (15.7 (2.6) v 14.0 (3.3) mg/l, RIPC v control; p = NS). However, sub-group analysis on the basis of statin use showed that the highest rise was in the group of patients with RIPC not taking statins and was significantly greater than in patients with RIPC taking statins (23.8 (3.71) v 11.4 (3.0) mg/l, respectively, p<0.01). Both CK-MB and TNI leakage were raised (slightly but significantly) after PCI in controls at 24 h compared with baseline values. However, this small rise was significantly worse after RIPC (CK-MB, 1.33 (0.27) v 3.57 (0.97) ng/ml, p<0.01; TNI, 0.255 (0.059) v 0.804 (0.232) ng/ml, p<0.05, respectively at 24 h). The increase was more marked in the RIPC subgroup not taking statins. Conclusions: RIPC does not reduce, but exacerbates, the enzyme and TNI release from the heart after single-vessel angioplasty with stent. Furthermore, the increased circulating CRP remains raised. It seems that there is an enhanced inflammatory response after RIPC in the absence of statin treatment.